A comparative analysis of sustainability of the usual food intakes of the Iranian population, Iranian food-based dietary guidelines, and optimized dietary models - Sobhani, Seyyed Reza; Edalati, Sareh; Eini-Zinab, Hassan; Kennedy, Gina; Omidvar, Nasrin (Frontiers in Sustainable Food Systems, 2022)
Promoting sustainable diets is a way to ensure sustainable development goals. Considering the importance of national food based dietary guidelines (FBDGs), this study aimed to assess and compare the sustainability dimensions of the usual Iranian dietary intakes with sustainable optimal diets, based on Iranian FBDGs (2006 and 2015 versions), Mediterranean and vegetarian FBDGs. Usual dietary intakes of Iranian households were estimated using household expenditure survey data. Diet sustainability, including environmental (water, carbon and land) footprints, cost and nutrient rich food (NRF) index were calculated for the usual diet and compared with those of the FBDGs. Using linear and goal programming, optimal food models were calculated through minimizing environmental footprints and cost, and maximizing NRF, simultaneously for each FBDG, while maintaining nutritional considerations recommended by the FBDGs. Replacing the usual dietary intake of Iranians with the optimal diet based on the 2016 Iranian FBDG was associated with reductions equal to 20.9 % for water footprint, 22.48 % for carbon footprint, 20.39 % for land footprint, 31.83 % for cost, and 7.64 % increase in NRF index. The optimal model based on 2016 Iran FBDG was 10% more sustainable compared with the 2005 version Changing usual consumption of Iranians to the optimal model based on the Mediterranean pyramid was accompanied with the highest NRF index, lower environmental footprints and cost compared to other models. The recent Iranian FBDG compared with the older one, was more sustainable. Considering the dimensions of a sustainable diet for future FBDGs revisions is recommended.